(untitled) (Decentering European studies: perspectives on Europe from its beyond, 2025)
The two chapters in this section aim to answer a broad research question from an international perspective: to what extent does integrated healthcare policy reform impact policy design and people’s living conditions? Integrated healthcare reforms have aimed at addressing global concerns about the consequences of the demographic and epidemiological transitions, taking into account the increased threat of fragmented healthcare service delivery and mounting healthcare expenditures. Through a comparative lens, the chapters here focus on the Chinese and European welfare states to address why integrated healthcare reform is key, the different reform paths taken, and their policy outcomes. The chapters provide new insight into―and social recognition of―the specific social policy fields that currently affect the directions taken in healthcare policy development globally and the populations at risk for sliding into poverty based on access to healthcare. These issues were already relevant before COVID-19 and have remained so during the pandemic. Together, the two chapters also present deviations regarding the definition of policy integration.